A numerical method for the solution of plane crack problems in finite media - P. S. Theocaris; N. Ioakimidis (International Journal of Mathematics and Mathematical Sciences)
A general method for the solution of plane isotropic elasticity crack problems inside a finite medium of arbitrary shape or an infinite medium with holes of arbitrary shape is presented. This method is based on the complex potential approach of plane elasticity problems due to Kolosov and Muskhelishvili [1] and makes no assumption on the way of loading of the cracks and of the other boundaries of the medium.